Net interoffice accounts of global banks: The role of domestic funding - Carmela D'Avino (International Journal of Financial Studies, 2015)
Existing literature has identified domestic restrictive monetary policy and deteriorating funding conditions as the predominant factors explaining the increase in net interoffice accounts of global banks, that is, the net liabilities of parent offices due to their related foreign offices. The purpose of this research is twofold. Firstly, it quantifies the responsiveness of net interoffice accounts to variations in different types of domestic funding. Secondly, the paper assesses whether the relationship between net interoffice accounts and domestic policy-steered rates depends on cross-sectional differences in the funding structure of global banks. Using US banks' balance sheets data collected by the Federal Financial Institutions Examination Council, the results highlight the importance of domestic repo borrowings in explaining net interoffice accounts, especially for larger banks during the crisis. On the other hand, a negative relationship between policy rates and net interoffice accounts is observed only for those global banks with a relatively higher share of repo borrowings.
Keywords: F33; F34; F42; G21; 330; US global banks; bank funding; monetary policy; repurchase agreements; panel data